2014
DOI: 10.5901/mjss.2014.v5n27p88
|View full text |Cite
|
Sign up to set email alerts
|

Compensation Management and Motivation: Cooking utensils for Organisational Performance

Abstract: The achievement of organisational performance is essential for sustainability and continuous existence of the organisation. Obviously, this is a function of employees that are well remunerated and motivated, thus, it is contingent that compensation management and employees motivation should be aligned with the vision, mission and objectives of the organisation. In doing this, the attainment of organisational performance becomes an easy task and it will also reduce the antecedent negative impact of absenteeism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 49 publications
2
29
0
5
Order By: Relevance
“…Similar to the results found by Njoroge et. al [27] which showed that there is a strong relationship between compensation and work performance which is also supported by other studies [24,34,39,40].…”
Section: -3-the Effect Of Compensation On Business Existencesupporting
confidence: 74%
See 1 more Smart Citation
“…Similar to the results found by Njoroge et. al [27] which showed that there is a strong relationship between compensation and work performance which is also supported by other studies [24,34,39,40].…”
Section: -3-the Effect Of Compensation On Business Existencesupporting
confidence: 74%
“…The compensation provided can be in the form of salary, commission, bonus and stimulus [23]. The ultimate goal of compensation is to improve organizational productivity and performance of employee which leads to an increase in the company's competitive ability [24]. Likewise, research [16,[25][26][27] which shows that there is a noticeable impact of compensation on work motivation as well as commitment.…”
Section: -Literature Reviewmentioning
confidence: 99%
“…Ahlstrom and Bruton (2010, p. 200) referred to it as ''thrust for individual's exploits that rejuvenates and guides goal-oriented behaviour''. Similarly, motivation is described as a propeller that strengthens behaviour, offers attitudinal path and inspires consistency as worker meets serious encounters (Grobler, Wärnich, Carrell, Elbert & Hatfield, 2011;Mathis & Jackson, 2011;Adeoye & Elegunde, 2014;Brevis & Vrba, 2014). Ramlall (2004, p. 53) coined it as ''keenness to utilise extraordinary effort towards organisation's goals, conditioned by the efforts ability to satisfy some individual need''.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The impact of a conducive environment on institutional performance and success cannot be underestimated, and as posited by Adeoye and Elegunde (2012), organizations are starting to recognize environmental performance as a source of competitive advantage. Just like other business organizations, academic libraries also operate within two major types of environment, that is, internal and external environment.…”
Section: Introductionmentioning
confidence: 99%